Pengaruh Penggunaan LKPD Berbasis Agrosains terhadap Kemampuan Argumentasi Ilmiah pada Pembelajaran IPA Siswa SMP - Cindy Laura Kenzi; Supeno Supeno; Iwan Wicaksono (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
This study aims to determine the effect of the use of agroscience-based Student Worksheets (LKPD) on junior high school students' scientific argumentation skills on ecology and biodiversity. The main problem raised is the low scientific argumentation skills of students, which impacts on suboptimal critical thinking skills and the delivery of opinions based on scientific evidence. The research method used was a quasi-experimental with a nonequivalent control group design, involving two classes, namely the experimental class using agroscience-based LKPD, and the control class using conventional LKPD. The research instrument was a pre-test and post-test essay test that measured three indicators of scientific argumentation, namely claim, evidence, and justification. Data were analyzed using normality tests, homogeneity tests, t-tests, and N-Gain analysis. The results showed a significant difference between the experimental and control classes. The average N-Gain of the experimental class was 0.73 (high category), while the control class was 0.44 (medium category). The largest increase occurred in the justification indicator in the experimental class. The conclusion of this study is that the use of agroscience-based student worksheets (LKPD) is effective in improving students' scientific argumentation skills, particularly in developing logical and evidence-based scientific justifications. It can also serve as an alternative, innovative teaching material to improve the quality of science learning in schools.